AV-101, a novel inhaled dry-powder formulation of imatinib, in healthy adult participants: a phase 1 single and multiple ascending dose study. Issue 2 (13th March 2023) - Gillies, Hunter; Niven, Ralph; Dake, Benjamin T.; Chakinala, Murali M.; Feldman, Jeremy P.; Hill, Nicholas S.; Hoeper, Marius M.; Humbert, Marc; McLaughlin, Vallerie V.; Kankam, Martin
Background: Oral imatinib has been shown to be effective, but poorly tolerated, in patients with advanced pulmonary arterial hypertension (PAH). To maintain efficacy while improving tolerability, AV-101, a dry powder inhaled formulation of imatinib, was developed to deliver imatinib directly to the lungs. Methods: This phase 1, placebo-controlled, randomised single ascending dose (SAD) and multiple ascending dose (MAD) study evaluated the safety/tolerability and pharmacokinetics of AV-101 in healthy adults. The SAD study included five AV-101 cohorts (1 mg, 3 mg, 10 mg, 30 mg, 90 mg) and placebo, and a single-dose oral imatinib 400-mg cohort. The MAD study included three AV-101 cohorts (10 mg, 30 mg, 90 mg) and placebo; dosing occurred twice daily for 7 days. Results: 82 participants (SAD n=48, MAD n=34) were enrolled. For the SAD study, peak plasma concentrations of imatinib occurred within 3 h of dosing with lower systemic exposure compared to oral imatinib (p<0.001). For the MAD study, systemic exposure of imatinib was higher after multiple doses of AV-101 compared to a single dose, but steady-state plasma concentrations were lower for the highest AV-101 cohort (90 mg) compared to simulated steady-state oral imatinib at day 7 (p=0.0002). Across AV-101 MAD dose cohorts, the most common treatment-emergent adverse events were cough (n=7, 27%) and headache (n=4, 15%). Conclusions: AV-101 was well tolerated in healthy adults, and targeted doses of AV-101 significantly reduced the systemic exposure of imatinib compared with oral imatinib. An ongoing phase 2b/phase 3 study (IMPAHCT; clinicaltrials.gov identifier NCT05036135) will evaluate the safety/tolerability and clinical benefit of AV-101 for PAH. AV-101, a dry-powder inhaled formulation of imatinib, reduces systemic exposure to imatinib versus oral imatinib and is well tolerated in healthy adults. An ongoing phase 2b/3 study will evaluate AV-101 in patients with pulmonary arterial hypertension. https://bit.ly/3Tlh6ru